The devil and miss Prym - Coelho, Paulo; Caistor, Nick; Hopkinson, Amanda (Thorsons, 2003)
A community devoured by greed, cowardice and fear. A man persecuted by the ghosts of his painful past. A young woman searching for happiness. In one eventful week, each of them will face questions of life, death and power, and each of them will have to choose their own path. Will they choose good or evil? Coelho dramatizes the struggle with every soul between light and darkness, and its relevance to our everyday struggles: to dare to follow our dreams, to have the courage to be different and to master the fear that prevents us from truly living